MANAJEMEN PUSTAKAWAN PADA DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN ACEH TENGAH - Bensu Elianita; niswanto .; Sakdiah Ibrahim (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
The library is one of the means providing various collections of information in fulfilling and supporting the success of education quality. The quality of the library can be seen from the librarian’s management in managing the library. The purpose of this research waswas to know the planning and procurement of library collections, classification, and catalog of library collections, library system for visitor service, monitoring and evaluation of library activities program. The approach used in this study waswas a qualitative approach. The technique of collecting data was done through observation and interview. The subjects of research were the head of regional office of library and ten librarians. The results of the study indicated that: (1) the planning waswas done based on the needs of visitors, and the collection procurement system waswas done based on the analysis of visitor needs which was then conducted through routine project, purchasing, assistance, and publisher cooperation through APBK (regional revenue and expenditure budget); (2) the classification system for library collection was done in accordance with guidelines DDC (dewey decimal classification); (3) the service system used an open service system (open access). The open access does not run smoothly due to the limited space, where the reading room of children, adolescents, general, storytelling space and reference space are situated in one place; (4) supervision was carried out in every activity program while the evaluation was done at the end of the year. The supervision and assessment did not find the optimal result because it was not implemented based on the indicators made. Depending on the results of the study, it is recommended that the head of the library involve librarians in managing library management and pay attention to improving facilities and infrastructure so that the purpose and function of the library will work well.Keyword: management, librarian and library